(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article provides a comprehensive theoretical and methodological analysis of the role of artificial intelligence in the transformation of the methodology and organization of scientific research in the field of hotel and restaurant business. It is substantiated that in the conditions of digitalization of the economy, growth in data volumes and complexity of the competitive environment, traditional approaches to conducting scientific research need to be reconsidered and modernized. It is determined that the integration of machine learning algorithms, tools for processing large data sets, automated analysis and forecasting systems forms a new digital paradigm of research activities in the field of hotel and restaurant business. The impact of artificial intelligence technologies on the key stages of the scientific process is investigated: the formation of scientific problems, the formulation of hypotheses, the collection and verification of data, analytical processing of information, modeling of enterprise development scenarios and interpretation of results. It is substantiated that the use of artificial intelligence allows to increase the accuracy of economic forecasts, reduce the level of subjectivity during the processing of empirical data, optimize time and resource costs, and ensure the scalability of analytical procedures. Particular attention is paid to the organizational aspects of the digitalization of scientific research, in particular the use of integrated information systems, analytical platforms, cloud services and tools for automated visualization of results. The author’s structural model of the integration of artificial intelligence into the scientific research system is proposed. The transformation of the role of the researcher is proven and the risks of using algorithmic technologies are outlined.